THE INFLUENCE OF INCOME ON HOUSEHOLD CAR AND MOTORCYCLE OWNERSHIPS IN DENPASAR CITY, BALI - Wedagama, D. M. Priyantha (Jurnal Ilmiah Teknik Sipil, 2012)
Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 A bstract: This study investigates t he influence of household income on both car and motorcycle ownerships in the city of Denpasar using a Multinomial Logit Model. The household income is about 61%, 17% and 61% more likely to influence a household owning 1 motorcycle and 1 car, 2 or more motorcycles and 0 car, and 2 or more motorcycles and 1 car respectively than 1 motorcycle and no car. The probability of both car and motorcycle ownerships increases substantially by more than 4% in the next 20 years if household income in Denpasar city rises. This is particulary applied for the household owning 1 motorcycle and 1 car and 2 or more motorcycles and 1 car. The probability of a household owning 1 motorcycle and no car ownership however, drops significantly by almost 10% in the next 20 years if household income in Denpasar city increases. Consequently, the household income significantly influences both car and motorcycle ownerships in the city of Denpasar. A huge number of car and motorcycle uses on the road continously leads to serious transport problems in the city of Denpasar for the next few years. This is related to the negative impacts of transport in particular road safety and environmental impact. Improving the existing public transport and introducing a high quality public transport service within and to/from Denpasar city is urgently required. The fare of such high quality public transport service in Denpasar city however, must be sufficiently low to compete with the cost of riding a motorcycle. In addition, a significant amount of fare subsidy from both local and central government is considerably required /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Household Income, Motorcycle, Car, Ownerships.